How is enterprise cope with sudden crisis: Testing the moderation role of COVID-19 crisis towards ERM disclosure and firm value - Putra, Adli Zuliansyah; Widiastuti, Harjanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study investigates the moderating influence of the COVID-19 crisis on the relationship between risk management disclosure and firm value.Design/Methodology/Approach: 305 non-financial firms listed on the Indonesia Stock Exchange during 2019-2020 were analyzed, utilizing archived data from company annual reports according to purposive sample criteria. The data were further evaluated quantitatively by panel data regression analysis with Eviews12 to evaluate the overarching hypothesis.Research findings: The results indicate that risk management disclosure benefits firm value; however, the COVID-19 crisis does not influence this connection. It indicates that disclosure functions as a signaling mechanism to preserve investor trust rather than serving as a primary source of information during crises. Theoretical contribution/ Originality: This research highlights the COVID-19 pandemic's role in reinforcing the necessity for risk management disclosure to mitigate information asymmetry and serve as a favorable signal for shareholders and investors while contributing empirical insights into the crisis's influence on corporate risk disclosure practices in sustaining firm value.Research limitation/Implication: This research highlights the need to develop a risk management framework that is more adaptive to unexpected extraordinary events, such as the pandemic crisis. It is done to increase the relevance of information needed by potential investors and company owners so that the effect of risk management disclosure can be seen during the new crisis.